Analysis of Students’ Strengths and Weaknesses in Academic Writing at Universitas PGRI Kalimantan - Nana Suciati; Tri Winindyasari Palupi; Ida Rusdiana (UMBanjarmasin, 2024)
Academic writing is an essential skill for academics. It enables students, researchers, and academics to communicate ideas, and disseminate research findings. Thus, academic writing is included as one of the courses of the writing cluster subjects at the English Study Program at University of PGRI Kalimantan. The final goal of this course is that students can write a scientific essay that comes from simple research. The study is carried out to define the strengths and weaknesses that are mostly made by students’ Academic Writing Subject. This is a descriptive research, which is in conceptual content analysis method. The samples are taken from 16 students’ scientific essays in Academic Writing Course. The findings are that students are good in ethical standards, structured format, as well as clarity and precision. However, they are lack of critical thinking and evidence-based arguments. It is suggested that in advanced teaching, students are provided with more activities involved critical thinking and evidence-based argument.